Numerical Simulation of Enhanced Solar Air Heater with Pcm and Aluminum Fins for Food Drying at Semi-Arid Zones - Castillo-Del Barrio, E; Diaz-Moreno, F (Elsevier Ltd, 2025)
The objective of this work is to enhance the thermal efficiency of a food-drying Solar Air Heater (SAH) using phase change material (PCM), two glass plates, and aluminum fins. The PCM acts as a passive thermal energy storage system that extends the operating time of the SAH, managing to achieve and sustain the drying temperature without using external energy sources. The design parameters studied are: (1) the length of the SAH; (2) the thickness of the PCM; (3) the selection of a thermal insulation system (single or double glass), and (4) the inclusion of aluminum fins in the PCM cavity to increase the heat transfer rate between the absorber and the PCM. Each system is studied for an entire day–night cycle (24 h) of a typical summer day in the south hemisphere (December), selecting the city of Vicuña, Chile (semi-arid climate) as the place of study. We consider variable in-time atmospheric solar irradiation conditions, air temperature, and wind velocity in the physical–mathematical model. A total of 29 configurations are studied numerically using the Finite Volume Method and evaluated by energy and exergy analyses. The most efficient configuration is selected by comparing the time the SAH-PCM operates and the additional energy required to reach the minimum operating temperature during the entire cycle. The results indicate that the most efficient SAH configuration includes a 2 m length, double glass system, fins, and 4 cm PCM. This configuration requires 1.5 times less energy to operate on a 24-hour cycle (-1.4 kWhr) than the 2 m base case configuration and extends its operating time by 0.7 hr. In addition, the average daily energy and exergy efficiency increased by 1.8 and 1.5 times, respectively. © 2024 Elsevier Ltd